A study on surface wash and runoff using open system erosion plots - Syed Abdullah, Sharifah Mastura; Al-Toum, Sabry (Universiti Putra Malaysia Press, 2000)
This study on surface wash and runoff using open system erosion plots was carried out in Tekala forest reserve, Hulu Langat, Selangor. Variations in the rates of surface wash and runoff were analysed with reference to soil characteristics of the site and 14 rainfall parameters. The results showed that the rate ofsurface wash ranged from 49.5 g m-2 yr1 to 137 g m-2 yr1 with an average of 85.04 g m-2 yr1 • Suspended sediment constituted approximately 80% of the total sediment transported 1Yy surface wash. The average rate of total surface runoff was 133.8 lm-2 y£l. The results also showed that correlations between surface wash, surface runoff and soil characteristics varied. However, the correlation between surface runoff and surface wash was found to be highly significant with most rainfall parameters. The total amount of rainfall was most suitable rainfall parameter to predict both surface wash and runoff